Folate, B12 and Iron Levels in COVID 19 Patients Observational Case-Control Study - İsmail Anaç; Burcu Timur; Yakup Gezer; Ahmet Doğan (Sağlık Akademisi Kastamonu)
Background: Folic acid, B12 and Iron play an important role in the pathogenesis of viral infections. Aim: The aim of the study is to determine the blood levels of Folate, B12 and Iron and to examine their relationship with prognosis in cases followed up by the COVID 19 pandemic service. Materials and Methods: The study was planned as a retrospective observational case-control study. In a period of approximately 3 months, 140 patients were screened retrospectively, 70 of whom were COVID 19 and 70 control cases. Cases